Hubungan Kualitas Tidur Dengan Tekanan Darah Pada Laki-Laki Penderita Obesitas Sentral Di Lingkungan Universitas Lampung - Ester Krisdayanti; Khairun Nisa Berawi; Emantis Rosa (Medula, 2022)
Obesity has a tendency to develop throughout the world, both in developed and developing countries. This is due to the prevalence which continues to increase preogressively from year to year. This central obesity is closely related to degenerative diseases such as hypertension that occur through the mechanism of Renost Angiotensin Aldostseron and sympathetic nerve activity. Poor sleep quality can increase the increase in blood pressure so that it worsens the development of hypertension in patients with central obesity. This type of research is a non-paired observational analytic type with cross sectional research design. This research was conducted in November 2012 in the University of Lampung. The sample used in this study was based on consecutive sampling and obtained as many as 80 men with central obesity. This research was conducted by interviewing the Pittsburgh Sleep Quality Index questionnaire and measuring blood pressure to respondents from all the academic community of men with central obesity selected in the University of Lampung. The results of this study were processed using computer software. The results of the analysis with Chi Square test of sleep quality on systolic blood pressure showed p value <0.05, namely p value 0.021 and PR 0.056 and 95% CI 0.320-0.932 and sleep quality on diastolic blood pressure obtained p values ​​0.013 and PR 0.531 and 95% CI 0.312-0.903. The conclusion of this study, there is a relationship between sleep quality and blood pressure in men with central obesity at Lampung University.